The Representation Of Women’s Labour In ‘Labour’ By Paris Paloma: A Feminist Perspective: Representasi Kerja Perempuan dalam “Labour” Karya Paris Paloma: Perspektif Feminis - Kesyha Rachel Suri; Sakarissa Khayra; Zahwa Shintya Pitaloka; Anaya Alysa Nabila; Fasha Naura Hasibuan; T. Thyrhaya Zein (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2026)
The research aims to identify the main forms of women’s labour represented in the lyrics and to explain how those representations reflect liberal feminism, existential feminism, and emotional labour theory. This study applies a qualitative descriptive design. The primary data are selected lyrical units from Labour, while secondary data are drawn from feminist theory, popular music studies, and scholarship on unpaid care work. Data were collected through documentation and library research, then analyzed using the Miles, Huberman, and Saldaña model through data collection, condensation, display, and conclusion verification. The findings reveal four interrelated themes: invisible domestic labour, emotional and reproductive burden, women’s otherness and autonomy loss, and feminist resistance. These themes show that the song reframes house-based service as labour rather than natural feminine devotion. The study concludes that Labour works as a feminist critique of domestic ideology by transforming private exhaustion into collective awareness. Its contribution lies in connecting feminist literary analysis, popular music criticism, and scholarship on unpaid labour to demonstrate how contemporary lyrics can expose gendered power in everyday domestic relations.